(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This study aimed to verify the relationships between depressive symptoms, social skills and academic competence of children and adolescents in the period of resumption of face-to-face classes during the COVID-19 pandemic. Participants were 66 children and adolescents, with a mean age of 10.9 years, most of whom (65.2%) were female. The collection took place in public and private schools in a city in the interior of Minas Gerais. The instruments used were the Childhood Depression Inventory (CDI) and the Social Skills, Behavior Problems and Academic Competence Inventory (SSRS-BR), self-assessment and teacher versions. Depressive symptoms affected nearly 26% of participants. Negative correlations were found between the degree of depressive symptoms and scores of social skills and academic competences. Children’s social skills were positively related to academic competence assessed by teachers. Comparisons between groups showed that female children, public school children and older children were more likely to develop indicators of depression.